2023
DOI: 10.1021/acssuschemeng.3c02641
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Carbon Dots in a Core–Shell Mesh through Coaxial Direct Ink Writing for Improved Crop Growth

Isik Arel,
Ayse Ay,
Jingyi Wang
et al.

Abstract: Through coaxial direct ink writing, we fabricated a core−shell mesh system for the controlled release of carbon dots (C-dots). In the core ink, we developed an ink formulation with tuned viscosity using hydroxypropyl cellulose and polyethylene glycol to host C-dots. Polycaprolactone was employed as the main shell material, in combination with sodium alginate, to control the degradation rate of the shell. We investigated the degradation profile of the 3D-printed meshes and tracked the weekly release of C-dots i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…23 Many studies have shown that CDs have great potential in promoting plant growth, such as promoting growth and development, regulating plant photosynthesis, and improving plant stress resistance. 24–29 Kou et al have discovered that the activation of aquaporin-encoding genes by CDs can expedite seed germination, stimulate roots and hypocotyl elongation in seedlings, and enhance mineral element absorption and photosynthesis to improve both yield and nutritional quality in mature plants. 30 Tan et al have found that 100 mg L −1 N-CDs increased the chlorophyll a content by 12.68%, electron transport rate by 38.61%, and Rubisco activity by 60.61%, which significantly promoted the biomass accumulation (41.70%) and increased the nutrient content of lettuce.…”
Section: Introductionmentioning
confidence: 99%
“…23 Many studies have shown that CDs have great potential in promoting plant growth, such as promoting growth and development, regulating plant photosynthesis, and improving plant stress resistance. 24–29 Kou et al have discovered that the activation of aquaporin-encoding genes by CDs can expedite seed germination, stimulate roots and hypocotyl elongation in seedlings, and enhance mineral element absorption and photosynthesis to improve both yield and nutritional quality in mature plants. 30 Tan et al have found that 100 mg L −1 N-CDs increased the chlorophyll a content by 12.68%, electron transport rate by 38.61%, and Rubisco activity by 60.61%, which significantly promoted the biomass accumulation (41.70%) and increased the nutrient content of lettuce.…”
Section: Introductionmentioning
confidence: 99%